Comparison of coaching behaviors between individual sports and team sports - Zeng, Z. H.; Liu, W.; Hipscher, M. (Research Quarterly for Exercise and Sport, 2008)
While considerable research has been conducted addressing coaching behaviors in team Sports (Myers, Wolfe, & Feltz, 2005), little literature is available addressing coaching behaviors in individual sports and comparing coaching behaviors in individual Sports (ISs) with those in team sports (TSs). Given contrasting characteristics between ISs and TSs, coaching behaviors in these two sports categories might be different to some degree. The purpose of this study was to compare coaching behaviors betvveen coaches of ISs and those of TSs. Participants were 5 head coaches in individual sports (track and field, gymnastics, etc.) and 5 head coaches in team sports (basketball, soccer, etc.) from a college in the U.S. A total of 20 training sessions (2 training sessions for each coach) were videotaped and coded using Arizona State University Observation Instrument (Lacy & Darst, 1989), which contained 11 predefined coaching behaviors. Event recording technique was used to produce rate per minute (RPM) for each of the eleven coaching behaviors. A one-way multivariate analysis of variance revealed significant differences in five coaching1 behaviors between the two types of coaches. Specifically, ISs coaches demonstrated significantly greater (p < .05) RPM than did TSs coaches in preinstruction (M= 1.41 + .12vs, ,73± .13),questioning (M = .55 ± .11 vs. .29 ± .31), and praise (M = .84 ± .37 vs. .36 ± .38), and TSs coaches demonstrated significantly larger (p < .05) RPM than ISs coaches in postinstruction (M= 1.28 ± .18 vs. .56 ±.06) and hustle (M= .89 + .12 vs. .13 ± .06). No significant differences (p> .05) were identified in concurrent instruction, positive modeling, negative modeling, scold, management, and uncodeable coaching behaviors between the two groups. It seems the findings match contrasting characteristics of the two Sports categories to some degree. ISs usually take place in a relatively fixed, predictable condition and Preinstruction is more likely to happen than Postinstruction. In contrast, TSs happen in an open, unpredictable condition and Postinstruction is more needed for adjustments and feedbacks after each episode of a training Session. In addition, given the large number of athletes who are expected to cooperate appropriately with each other in TSs, coaching TSs might be more challenging and demanding in providing feedback and instruction and, therefore, more Hustle behaviors occurred. More research is needed to understand differences further in coaching behaviors between ISs and TSs.